POLEMIK DALAM KEPUTUSAN PRESIDEN NOMOR 114/P/2022 - Riska Ari Amalia; Ashari Ashari (UNES Law Review, 2023)
Controversy ensued when the public judged that the President had turned a blind eye to the unconstitutional removal of Aswanto by issuing a policy on dismissing Aswanto and at the same time appointing Guntur judges, namely Presidential Decree Number 114/P/2022 concerning Dismissal and Appointment of Constitutional Court Judges. Based on this, problems were found, regarding the validity of a state administrative decision and how the validity of Presidential Decree Number 114/P/2022 concerning Dismissal and Appointment of Constitutional Court Judges. The research method used is normative juridical method, using statutory approach, case approach, and conceptual approach. The results of the study show that the KTUN has validity if it fulfills the material and formal requirements, as well as the conditions specified in Article 52 of Law Number 30 of 2014. Then Presidential Decree Number 114/P/2022 concerning Dismissal and Appointment of Constitutional Court Judges is invalid because it does not comply with the provisions in Article 52 paragraph (2) of Law Number 30 of 2014.